The Delivery of Diagnosis by Child Psychiatrists: Process Characteristics and Correlates of Distress - Brand-Gothelf, Ayelet; Hasson-Ohayon, Ilanit; Hertz-Palmor, Nimrod; Basel, Dana; Gothelf, Doron; Karnieli-Miller, Orit (Frontiers in Psychiatry, 2021)
We describe the attitudes of child psychiatrists toward diagnosis delivery (DD) and explore potential stressful factors associated with the process. Eighty Israeli child psychiatrists completed a questionnaire on their perceptions of DD of schizophrenia, autism spectrum disorder (ASD), and attention deficit/hyperactivity disorder (ADHD). We also conducted semi-structured in-depth interviews with 12 child psychiatrists who were asked to share their personal experience with DD. The questionnaire responses revealed that child psychiatrists perceived schizophrenia and ADHD as the most and least severe disorders, respectively, and that its treatment as being ineffective and effective, respectively. They expressed negative perceptions toward DD of schizophrenia and positive perceptions toward DD of ADHD. The results of linear regressions revealed that some factors predicted distress accompanying DD in all three diagnoses, such as lack of professional experience, negative perceptions of DD, and the effect of parents' attitudes of opposition to the diagnosis. The interviews revealed that DD was often described by psychiatrists as an emotional experience, and that the psychiatrists' age, and whether the psychiatrist’s identified more with the child or the parent, affected their attitude towards DD. Lastly, the psychiatrists expressed feelings of loneliness in the procedure of DD and their wish to share and reflect on their experiences with others. These findings may contribute to a better understanding of the clinically important topic of DD in child psychiatry that has not been adequately addressed and help deal with psychiatrists' challenges in this task.